2016
DOI: 10.1111/juaf.12226
|View full text |Cite
|
Sign up to set email alerts
|

Gentrification and the Right to the City: Community Conflict and Casinos

Abstract: Henri Lefebvre's right to the city concept is increasingly used to challenge the development prerogatives associated with neoliberal development. These challenges are more common as gentrification becomes a global urban strategy. This article is an empirical investigation that examines competing claims to community legitimacy and authenticity in a conflict over gentrification in a Philadelphia neighborhood. This conflict emerged in Fishtown when long‐time established residents went head to head with upper‐inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…An often-discussed benefit of gentrification is the reintroduction of resources to impoverished neighborhoods due to an increase in the proportion of middle and upper-class households. These resources range from better quality food options to the local presence of health clinics [ 9 , 23 , 24 ] The greater availability of resources associated with this transition should be associated with improvements to quality of life and in turn better self-rated health. In addition, more affluent neighborhoods are strongly associated with social cohesion and networks that improve care [ 25 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…An often-discussed benefit of gentrification is the reintroduction of resources to impoverished neighborhoods due to an increase in the proportion of middle and upper-class households. These resources range from better quality food options to the local presence of health clinics [ 9 , 23 , 24 ] The greater availability of resources associated with this transition should be associated with improvements to quality of life and in turn better self-rated health. In addition, more affluent neighborhoods are strongly associated with social cohesion and networks that improve care [ 25 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research documented a few examples of gentrification-related residential displacement, [32][33][34] while quantitative studies were unable to demonstrate that gentrification led to widespread displacement. 6,28,35,36 Even if gentrification has not been proven to result in residential displacement, the fear of displacement has been found to make incumbent residents psychologically distressed that they will be displaced, which in turn should be associated with lower SRH. 6,29,32 Beyond residential displacement, gentrification discussions also highlighted concerns among incumbent residents changes in the types of amenities in the neighborhood was the result of cultural displacement.…”
Section: Introductionmentioning
confidence: 99%
“…For example, gentrification is often heralded for improving access to neighborhood amenities and city services due to the growing representation of middle-and upper-class residents. [28][29][30] Further, recent research on the association of gentrification and violent crime found that gentrification was negatively associated with violent forms of crime. 32,33 While the results of these studies had implications for health research, the direct benefits of gentrification for SRH have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Consider, for example, Balzarini and Shlay's (forthcoming) analysis of how the development of a casino divided a gentrifying neighborhood. The casino was supported by older, poorer residents who saw it as a source of employment, but opposed by newer, wealthier residents over concerns that it would negatively impact surrounding businesses.…”
Section: Resultsmentioning
confidence: 99%